MODAL SOSIAL DAN EKOWISATA: STUDI KASUS DI BANGSRING UNDERWATER, KABUPATEN BANYUWANGI - Kusuma, Uma Adi; Satria, Dias; Manzilati, Asfi (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
This study investigates the role of social capital in the development of ecotourism in Bangsring Underwater, Banyuwangi. This study uses a qualitative approach to explore the role of social capital in supporting ecotourism development. Social capital has a positive influence in the success of empowerment programs conducted to the fishermen in changing fishing patterns and preserving the marine environment. Lastly, a strong social capital in the community can reduce the transaction costs. Keywords: Social Capital, Ecotourism dan Transaction Costs